Kinetic and equilibrium modeling for adsorption of textile dyes in aqueous solutions by carboxymethyl cellulose/poly(acrylamide‐co‐hydroxyethyl methacrylate) semi‐interpenetrating network hydrogel. Issue 11 (5th March 2013) - Bhattacharyya, Ruma; Ray, Samit Kumar; Brostow, Witold; Schubert, Dirk; Blagojevic, Snja Lucic
<x xml:space="preserve">Abstract</x> Semi‐interpenetrating network (IPN) hydrogels were synthesized by free radical copolymerization of acrylamide (AM) and hydroxyethyl methacrylate (HEMA) in aqueous solution of sodium carboxy methyl cellulose (CMC). The hydrogels were crosslinked with N, N′‐methylene bisacrylamide (NMBA). Hydrogel was also synthesized from copolymerisation of AM and HEMA. This was designated as PAMHEMA. All of these hydrogels were characterized by Fourier transforms infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), X‐ray diffraction (XRD), mechanical properties, and equilibrium swelling in deionized water. These hydrogels were used for adsorption of two important textile dyes, i.e., basic fuchsin and methyl violet from water at different experimental conditions. These hydrogels were found to show high removal% and adsorption of these two dyes from water for both low and high feed concentration range. Experimental dye adsorption data were fitted to five kinetic and seven adsorption model equations with non‐linear fittings. The experimental data were observed to fit well to most of these model equations because of non‐linear fitting. POLYM. ENG. SCI., 53:2439–2453, 2013. ©2013 Society of Plastics Engineers